X-MEN AMAZING : ONCE AND FUTURE JUGGERNAUT / 3 - Tynion, James, IV.; Jim'enez, Jorge, penciler; Rosenberg, Rachelle (New York : Marvel, 2015)
We've all heard the phrase "those are big shoes to fill." That's especially true when those are the massive boots of the unstoppable Juggernaut! When the Gem of Cyttorak reappears, seeking to create a new avatar, none hear its call more than those who have previously housed Cyttorak's power, Cain Marko and Colossus. But they aren't the only ones hunting for the Gem. Can the X-Men find it before it's too late? And can Colossus resist the temptation of Cyttorak's power? "Unstoppable" takes on a whole new meaning as Cyttorak's gem is finally located. The Juggernaut rises ... and the X-Men fall! Plus, a death in Storm's family sends the X-Men to Africa! Anole's deepest fears are unleashed on the streets of New York City! And Nightcrawler and Mystique's relationship reaches a boiling point!
"Marvel NOW!"--Cover.
Keywords: X-Men (Fictitious character) -- Comic books, strips, etc; Graphic novels